Analysis Of The Incidence Of Stunting In Toddlers In Terms Of Basic Immunization Status, Exclusive Breastfeeding History And History Of Infectious Diseases In The Sigompul Health Center Work Area - Siahaan, Maria; Hutasoit, Renni; Simamora, Lasria (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2023)
Stunting or short is one of the indicators of chronic nutritional status that describes stunted growth due to long-term malnutrition. Riskesdas data in 2018 shows the prevalence of stunting toddlers in Indonesia is 30.8%. Conditions in Indonesia based on data from the 2019 Study of Nutritional Status of Toddlers in Indonesia (SSGBI) are still relatively high, where the prevalence of stunting is 27.67%, this figure shows that stunting in Indonesia is still higher than the prevalence in Southeast Asia of 24.7%. This study is an observational analytical study research using a retrospective case control study design. The research was conducted in the Working Area of the Sigompul Health Center, Humbang Hasundutan Regency, from April - July 2022. The sample size in this study was 18 people and a control sample was taken with a ratio of 1: 1, namely 18 people. So the sample size was 36 people. The sampling technique in this study is Consecutive sampling. The results showed that basic immunization status was associated with stunting with a p value of 0.002<0.05; history of exclusive breastfeeding related to stunting with a p value of 0.007<0.05 ; while History of infectious diseases is not related to stunting with a p value of 0.658>0.05. It is expected for health workers in the Sigompul puskesmas work area to promote socialization and counseling about exclusive breastfeeding as well as basic immunization programs.